1986
DOI: 10.1128/aac.29.2.320
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and metabolism of E-5-(2-[131I]iodovinyl)-2'-deoxyuridine in dogs

Abstract: E-5-(2-lodovinyl)-2'-deoxyuridine (IVdU) is a potent inhibitor of herpes simplex virus type 1 replication in vitro. The selective antiviral activity of IVdU is due to pireferential phosphorylation by the herpes simplex virus type 1-encoded thymidine kinase. This selective sequesteration provided the rationale for the development of radioiodinated IVdU as a potential radiopharmaceutical compound for use in noninvasive diagnosis of herpes simplex virus encephalitis. We studied the pharimacokinetics and the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In HSV-1 TK gene-transduced tumor cells (KBALB-STK), the order of cellular uptake is [ 125 I]IVDU > [ 125 I]IVFRU > [ 125 I]IVFAU > [ 125 I]IVAU. Although [ 125 I]IVDU displayed the highest uptake in KBALB-STK cells at all time periods examined, it is considered unsuitable as an imaging agent due to its susceptibility to rapid, phosphorylase-mediated deglycosylation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In HSV-1 TK gene-transduced tumor cells (KBALB-STK), the order of cellular uptake is [ 125 I]IVDU > [ 125 I]IVFRU > [ 125 I]IVFAU > [ 125 I]IVAU. Although [ 125 I]IVDU displayed the highest uptake in KBALB-STK cells at all time periods examined, it is considered unsuitable as an imaging agent due to its susceptibility to rapid, phosphorylase-mediated deglycosylation …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with radiolabeled IVDU have demonstrated that, despite rapid accumulation in cells expressing HSV-1 TK in vitro , it is an unsuitable agent for in vivo detection of HSV-1 TK expressing tissue due to rapid phosphorylase-mediated deglycosylation …”
mentioning
confidence: 99%
“…However, post-mortem autoradiographic studies of rat brain showed that this was not a problem in the present model presumably because of the rapid clearance of radio-IVDU from the peripheral circulation [22]. Whilst rapid drug clearance is a useful parameter in the overall design of an imaging programme sufficient time must be allowed, post administration of radio-IVDU, for both clearance of nonmetabolized drug and for active sequestration into infected cells to take place.…”
Section: Discussionmentioning
confidence: 96%
“…Delivery of radio-IVDU to the anatomical site of interest in sufficient quantity and unaltered form is a significant problem. Radio-IVDU is rapidly cleared from peripheral circulation via renal excretion [22], the drug has poor lipid solubility [12] and the blood brain barrier (BBB) remains intact in this animal model of HSVE [12]. Following intravenous or intra-arterial injection, radio-IVDU is almost completely excluded from the brain.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these investigations, 2‘-deoxy-4‘-thionucleosides have been shown to have potent anti-herpes virus activities, and some analogues, especially 4‘-thiothymidine and 2‘-deoxy-4‘-thiocytidine ( 9 ), have been shown to possess potent cytotoxicity. ,, Notably, the 4‘-thionucleosides are resistant to hydrolytic cleavage of glycosyl linkage catalyzed by nucleoside phosphorylase . This is a major advantage of 4‘-thionucleosides, since several “4‘-oxy” antivirals have fatal drawbacks with regard to their metabolic stability caused by nucleoside phosphorylase . In addition, the potent antiviral activity and cytotoxicity of 4‘-thionucleosides suggest that they are well-recognized as substrates by both viral and host cells kinases.…”
mentioning
confidence: 99%